2006
DOI: 10.1146/annurev.neuro.29.051605.113009
|View full text |Cite
|
Sign up to set email alerts
|

NEURAL MECHANISMS OF ADDICTION: The Role of Reward-Related Learning and Memory

Abstract: Addiction is a state of compulsive drug use; despite treatment and other attempts to control drug taking, addiction tends to persist. Clinical and laboratory observations have converged on the hypothesis that addiction represents the pathological usurpation of neural processes that normally serve reward-related learning. The major substrates of persistent compulsive drug use are hypothesized to be molecular and cellular mechanisms that underlie long-term associative memories in several forebrain circuits (invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
1,834
2
47

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,346 publications
(1,922 citation statements)
references
References 201 publications
39
1,834
2
47
Order By: Relevance
“…However, when drugs of abuse are repeatedly used, behaviors related to sustaining the addiction may progressively supplant behaviors optimal for survival. This singleminded pursuit tends to undermine, rather than promote, species survival, effectively 'hijacking' the neural systems related to the pursuit of rewards (Hyman et al, 2006).…”
Section: Mesostriatal Acetylcholine and Reward Mediationmentioning
confidence: 99%
“…However, when drugs of abuse are repeatedly used, behaviors related to sustaining the addiction may progressively supplant behaviors optimal for survival. This singleminded pursuit tends to undermine, rather than promote, species survival, effectively 'hijacking' the neural systems related to the pursuit of rewards (Hyman et al, 2006).…”
Section: Mesostriatal Acetylcholine and Reward Mediationmentioning
confidence: 99%
“…1991; Hyman et al. 2006; Krasnova and Cadet 2009). Rodent studies have demonstrated that DAT and VMAT2 play important roles in reinforcing behaviors (Hall et al.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]. The vast number of clinical neuroimaging studies conducted on addicted individuals reveal striking abnormalities in prefrontal cortex (PFC) activity, relative to control subjects, that include reduced basal metabolic activity, reduced regional activation upon presentation of cues associated with non-drug primary reinforcers and enhanced metabolic activity upon presentation of drug-associated cues [e.g., [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%